Focalisation and its performative nature in John 3:1–21 - Hobyane, Risimati S. (HTS teologiese studies, 2024)
Without seeking to diminish its authority as the Word of God, this article acknowledges the Fourth Gospel as a brilliant piece of literary artistry by the implied author. The aim of this article is to substantiate this assertion by conducting a study on focalisation and illustrating how it invites the implied reader’s participation in the narrative. This contribution acknowledges the existence of insightful contributions on the topic, particularly in relation to the Fourth Gospel. However, it asserts that the study of the performative nature of focalisation in this particular Gospel has not received the attention it deserves. The main contribution of this article is its analysis of a selected narrative of the Fourth Gospel using focalisation as an analytical tool, with the objective of demonstrating that the Fourth Gospel is performative in nature, crafted and formulated to consistently engage the implied reader in considering its purpose, as stated in 20:30–31.Contribution: The article showcases that focalisation, when used as an analytical tool, can unlock, and enable the interpreter of the Fourth Gospel to recognise its performative nature to the implied reader of the text. This is critical, given that the text is crafted to encourage the reader to participate in it by making decisions regarding their faith in Jesus Christ.